PhET VIRTUAL LABORATORY ASSISTED E-MODULE DEVELOPMENT ON STATIC FLUID MATERIALS IN SMA/MA - Rugaya, Rugaya; Adellah, Nur ((IPER) Indonesian Physics Education Research, 2023)
This study aims to find out how the results of the development of the e-module are to determine the feasibility of the phet virtual laboratory-assisted e-module based on material experts, and media experts, and to find out the practicality of the phet virtual laboratory-assisted e-module based on the responses of students and physics teachers . The type of research used is research and development (R&D). The research model developed is ADDIE (Analysis, design, development, implementation, evaluation). The subjects in this study were all 37 students of class XI IPA at SMA PAB 4 Sampali. Based on the results of the trials that have been carried out, validation results are obtained from material experts with an average percentage score of 93% which is categorized as very feasible, while from the validation results of media experts with an average percentage score of 94% so that it is categorized as very feasible. Then to find out practicality can be seen from the percentage of scores on the response questionnaire of students who obtained a percentage score of 85%, while for the results the percentage score for physics teachers was 90%, so that overall the e-modules that have been developed are in the very practical category.